2001
DOI: 10.1142/s0217984901002695
|View full text |Cite
|
Sign up to set email alerts
|

A Study of 2d Ising Ferromagnets With Dipole Interactions

Abstract: A two-dimensional Ising model with competing short range ferromagnetic and long range dipolar interactions is used to study the transition properties and phase diagram in ultrathin magnetic films. Monte Carlo simulations in systems with exchange and dipolar interactions reveal a ground state of striped phases with varying width. By raising the temperature, the domain walls are smeared out by fluctuations, leading to a random domain mesoscopic phase with no long-range order, and finally the domains are melted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Of course, there is an increasing amount literature illustrating the conceptual and practical relevance of two dimensional (2D) systems with long range interactions [69][70][71]. The vibrational frequency of FCs contributions comes from both the symmetric and the asymmetric stretch and bending modes.…”
Section: The Vibrational Frequency (ω I ) and Propertiesmentioning
confidence: 99%
“…Of course, there is an increasing amount literature illustrating the conceptual and practical relevance of two dimensional (2D) systems with long range interactions [69][70][71]. The vibrational frequency of FCs contributions comes from both the symmetric and the asymmetric stretch and bending modes.…”
Section: The Vibrational Frequency (ω I ) and Propertiesmentioning
confidence: 99%
“…They can be a 2D dipolar lattice gas, 15 a 2D dipolar Ising model without vacancies [16][17][18][19][20][21] and with random vacancies, 22 a 2D frustrated system, 23 a bidimensional fluid system, 24 a 2D quantum Heisenberg model, 25 a density anomaly, 26 a spin-glass state, 27 correlations in fluids, 28 compositional patterns on bulk-immiscible alloy films, 29 and a colloidal fluid. 30 Our work is also based on this method.…”
Section: -13mentioning
confidence: 99%
“…The positive coupling constant A gives the strength of the long-range |R| −3 dipolar interactions due to electrostatic and elastic repulsions. [15][16][17][18][19][20][21] The ′ in the second sum means that i = j term is excluded, and ij[k] in the first term can be three-or more-site interactions 31,32 as well as pairwise interactions.…”
Section: Formalismmentioning
confidence: 99%
“…It has been supposed that one or more transitions could take place in the region between the ordered and paramagnetic phases. In particular, Ifti and coworkers [2] studied by numerical Monte Carlo (MC) simulations the behavior of specific heat, obtaining a curve with a sharp peak at temperature T 1 and a broad maximum in the region at T 2 ∼ 2T 1 . The authors suggested the existence of two possible phase transitions, the former related to the melting of the stripes, the latter to the occurrence of the paramagnetic phase.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for PFD, a careful examination of clusters proves to be useful in recovering, along new and more efficient lines, previously introduced parameters and criteria [1] [2]. Notations, definitions and elementary properties of C(M) and Z(M), as well as Shannon entropy, Hamming and Rohlin distances, are recalled in the Appendix, with some mathematical details.…”
Section: Introductionmentioning
confidence: 99%